AN ANALYSIS OF THE USE OF BRITISH ENGLISH AND AMERICAN ENGLISH TOWARD WRITING ABILITY IN THE STUDENTS’ INSTAGRAM ACCOUNTS OF NAHDLATUL ULAMA UNIVERSITY OF PURWOKERTO - Ade Christanty Yudha Bestari; Meilina Haris Mayekti; Dinar Faiza (Universitas Islam Nahdlatul Ulama Jepara, 2021)
This research contains an analysis of the use of British and American English on writing skills on student accounts of the Nahdlatul Ulama Purwokerto University (UNU Purwokerto). The purpose of this study was to determine the British English and American English vocabularies used by students in developing writing skills. This study uses a qualitative approach using descriptive analysis methods. The sampling technique was carried out by means of purposive sampling of the captions used for English writing practice. The Instagram account analyzed was the Instagram account of the Purwokerto Nahdlatul Ulama University students. The accounts analyzed were 50 students accounts. The results of this study are first, the researcher will record the vocabulary contained in the results of English Writing on the Instagram account and classify British and American English. So that we can understand the differences between British English and American English in the captions on students' Instagram. Second, the researcher will analyze writing skills regarding the suitability of grammatical with sentence context. Third, that this research can be used as a reference for British and American English knowledge that supports the process of developing English writing skills.